To solve the system of equations using substitution, we'll follow these steps:
- Solve one of the equations for one variable.
- Substitute that expression into the other equation and solve for the remaining variable.
- Substitute back to find the other variable.
Let's start with the equations:
- \( Y = -4x \)
- \( Y = 3x + 28 \)
Since both equations are equal to \( Y \), we can set them equal to each other:
\[ -4x = 3x + 28 \]
Now, we'll solve for \( x \).
- Add \( 4x \) to both sides:
\[ 0 = 3x + 4x + 28 \]
\[ 0 = 7x + 28 \]
- Subtract \( 28 \) from both sides:
\[ -28 = 7x \]
- Divide by \( 7 \):
\[ x = -4 \]
Now that we have \( x \), we substitute it back into one of the original equations to find \( Y \). We'll use \( Y = -4x \):
\[ Y = -4(-4) \]
\[ Y = 16 \]
Thus, the solution to the system of equations is:
\[ (x, Y) = (-4, 16) \]
So the final answer is:
\[ \boxed{(-4, 16)} \]